VIRAL PARTICLES TARGETING HEMATOPOIETIC STEM CELLS - STOPPATO, Matteo; BIASCO, Luca; CRUITE, Patricia (2025)
Provided herein are targeted lipid particles, such as targeted lentiviral particles, having a targeting agent that binds to a target molecule selected from the group consisting of ASCT1, ASCT2, CD105, CD110, CD117, CD133, CD146, CD164, CD34, CD46, CD49f, CD90, EPCR, and ITGA3, and related polynucleotides, cells, and methods for preparation and use of the targeted lipid particles, such as lenti viral particles. Also provided herein are methods involving mobilizing bone marrow cells in combination with administering targeted or non-targeted lipid particles, such as lentiviral particles, for treatment of a disease or condition in a subject.